2008
DOI: 10.1007/s12011-008-8139-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Serum Nickel and Homocysteine Concentration in Hemodialysis Patients

Abstract: Severe hyperhomocysteinemia (HHC) is associated with atherosclerosis. In hemodialysis (HD) patients, one of the main causes of death is cardiovascular disease. In animals, trace elements such as cobalt, copper, iron, and nickel ameliorated vitamin B(12) deficiency-induced HHC. However, correlations between plasma total homocysteine (tHcy) and trace elements in HD patients have not been investigated. Therefore, tHcy, folate, vitamin B(12), trace elements (cobalt, copper, iron, and nickel), and some laboratory p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 28 publications
3
7
0
1
Order By: Relevance
“…[15] Elevated levels of Homocysteine (eHcy or hyperhomocysteinaemia) occur with aging and decreased renal function. [14][15][16][17] Our study has observed a strong link between hyperhomocysteinaemia and ischaemic stroke. The findings are supported by recent study, which showed that hyperhomocysteinaemia was found in 48% of ischaemic stroke patients.…”
Section: Discussionmentioning
confidence: 70%
“…[15] Elevated levels of Homocysteine (eHcy or hyperhomocysteinaemia) occur with aging and decreased renal function. [14][15][16][17] Our study has observed a strong link between hyperhomocysteinaemia and ischaemic stroke. The findings are supported by recent study, which showed that hyperhomocysteinaemia was found in 48% of ischaemic stroke patients.…”
Section: Discussionmentioning
confidence: 70%
“…Krieg et al (2009) pointed out that serum folate, erythrocyte folate, and serum vitamin B 12 decreased as the blood lead concentration increased. Katko et al (2008) suggested that nickel might also be involved in the regulation of the methionine-folate cycle in humans. Tamura et al (2004) indicated that longterm, high-copper intake resulted in small but significant decreases in plasma concentrations of Hcy and folate.…”
Section: Discussionmentioning
confidence: 99%
“…Acute dermatitis was reported in a dialysis clinic using a nickel‐based stainless steel fitting in the pathway of the acid component of the dialysis bath (80). Of some comfort, perhaps, higher nickel levels have been linked to lower homocysteine levels in HD patients (81).…”
Section: Trace Element Concentrations: What Do They Mean?mentioning
confidence: 99%